RANCANGAN SISTEM INFORMASI PADA MADRASAH TSANAWIYAH SWASTA (MTS.S) JAUHARUL ISLAM BERBASIS WEB: Information System;MTs.S;Website;Profile;Education. - Susanto, Darex; Mulyadi; Karini, Mesy (LP2M Universitas Nurdin Hamzah, 2022)
This Web-based Information System has a very important role in the development of an agency, especially at the Private Madrasah Tsanawiyah (MTs.S) Jauharul Islam Penyengat Olak. The current academic system still uses the Agenda Book. Therefore, it is very necessary to have computer tools with computerized systems and the internet to speed up and minimize the problems that exist in the Private Madrasah Tsanawiyah (MTs.S) Jauharul Islam. The methods used in this research are Library Research, Field Research, Observation, Data Collection, System Analysis and Design, Application Development and Implementation. This research produces Information on Private Madrasah Tsanawiyah (MTs.S) Jauharul Islam Based on a Website so that it can make it easier for schools to promote or provide an overview of the profile of schools or educational institutions, and can make it easier for schools to process data, and student report cards.